DEVELOPMENT MANAGEMENT OF AGRICULTURAL ENTERPRISES - Т. Balanovskа; М. Mykhailichenko; V. Holik; К. Dramaretska; A. Troian (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. Today there is an intensification of activities and the associated increase in the dynamics of change in all sectors of the economy, including the agrarian sector, in Ukraine and throughout the world. This makes it urgently necessary for agricultural enterprises to adapt to such conditions in order to ensure the efficiency of their activities and long-term competitiveness. The most effective way to address this issue is to introduce development management of agricultural enterprises. The article considers the concept of «development» and «enterprise development», clarifies the meaning of the concept of «enterprise development management», and defines the purpose of such management. In accordance with the content and the proposed definition of the concept of «enterprise development management», the study highlights its characteristic features. It analyzes the main indicators of development of the agricultural enterprises in Ukraine, which demonstrated deterioration in the dynamics of their performance. The findings show the importance of development management of agricultural enterprises. To find a solution, the article suggests an algorithm for development management of agricultural enterprises that is developed, substantiated and based on the tools of strategic management. Adherence to such an algorithm will contribute to the effective realization of the potential of enterprises, rapid adaptation to changes in the external environment, the formation and implementation of effective development strategies, which will ultimately ensure economic, social and environmental efficiency and long-term competitiveness. The proposed algorithm is typical for agricultural enterprises of different organizational and legal forms of management, size, specialization, etc. and at the same time flexible to take into account the peculiarities of certain types of enterprises, which enables to achieve maximum efficiency of enterprise development on the basis of specification of its certain stages.